2019
DOI: 10.1111/mec.15051
|View full text |Cite
|
Sign up to set email alerts
|

The genomic pool of standing structural variation outnumbers single nucleotide polymorphism by threefold in the marine teleost Chrysophrys auratus

Abstract: Recent studies have highlighted an important role of structural variation (SV) in ecological and evolutionary processes, but few have studied nonmodel species in the wild. As part of our long‐term research programme on the nonmodel teleost fish Australasian snapper (Chrysophrys auratus), we aim to build one of the first catalogues of genomic variants (SNPs and indels, and deletions, duplications and inversions) in fishes and evaluate overlap of genomic variants with regions under putative selection (Tajima's D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
96
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(96 citation statements)
references
References 67 publications
0
96
0
Order By: Relevance
“…Nonrecombining sex chromosomes are extreme examples of supergenes extending entire chromosomes, many of which evolved through structural genomic mutations (e.g., the mammalian Y chromosome evolved through a series of inversions following the formation of the Sex-Determining Region Y gene) ( Lahn & Page 1999 ; Bachtrog 2013 ). There is emerging evidence that structural genomic variants might comprise the most important source of genomic variation in natural populations ( Mérot et al 2020a ), as they have been found to account for several times more variation, in terms of the number of affected nucleotides, than SNPs (e.g., 3× in the Australasian snapper [ Chrysophrys auratus ; Catanach et al 2019 ], 12× in Homo sapiens [ Pang et al 2010 ]).…”
Section: Eco-evolutionary Responses Hinge On Genetic and Genomic Archmentioning
confidence: 99%
“…Nonrecombining sex chromosomes are extreme examples of supergenes extending entire chromosomes, many of which evolved through structural genomic mutations (e.g., the mammalian Y chromosome evolved through a series of inversions following the formation of the Sex-Determining Region Y gene) ( Lahn & Page 1999 ; Bachtrog 2013 ). There is emerging evidence that structural genomic variants might comprise the most important source of genomic variation in natural populations ( Mérot et al 2020a ), as they have been found to account for several times more variation, in terms of the number of affected nucleotides, than SNPs (e.g., 3× in the Australasian snapper [ Chrysophrys auratus ; Catanach et al 2019 ], 12× in Homo sapiens [ Pang et al 2010 ]).…”
Section: Eco-evolutionary Responses Hinge On Genetic and Genomic Archmentioning
confidence: 99%
“…Pezer et al (2015) found that indels covered ~2% of an individual wild house mouse ( M. musculus domesticus ) genome compared to a reference genome, likely an underestimation considering that the analysis was based on variation of read depth only. The full characterization of standing genetic variation in a wild fish showed that levels of structural variation were threefold the levels of sequence variation (SNPs) across 12 individuals sequenced at high coverage (Catanach et al, 2019) . To this end, while the inclusion of our high coverage 10X Genomics dataset allowed us to characterize structural variation in a single individual, future work conducted at the population level will allow us to integrate more deeply the role of structural variation in the evolution of desert adaptation in the cactus mouse.…”
Section: High Genetic Diversity and Differentiationmentioning
confidence: 99%
“…Structural variants (SVs) are genomic rearrangements affecting the presence, position or direction of a nucleotide sequence, including deletions, duplications, insertions, inversion or translocations (Mahmoud et al, 2019). SVs are pervasive variants that shape genome architecture and they can cover a larger proportion of genetic variation than SNPs (Redon et al, 2006;Wellenreuther et al, 2019;Catanach et al, 2019). They have functional consequences, notably impacting the regulation of gene expression (Gamazon & Stranger 2015) and recombination rate by diminishing the frequency of meiotic crossing-over, which can preserve the integrity of an adaptive haplotype (Rowan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%